2009
DOI: 10.1637/8375-060908-resnote.1
|View full text |Cite
|
Sign up to set email alerts
|

Hemagglutinating Activity of Gallibacterium Strains

Abstract: In the present study, the hemagglutinating activity of seven reference strains, and nine Mexican and three Danish field isolates, of Gallibacterium was investigated by using fresh erythrocytes of 19 different types including chicken (broiler, rooster, layer hen), turkey, pigeon, quail, duck, Harris's hawk (Parabuteo unicinctus), house finch (Carpodacus mexicanus), cow, sheep, horse, dog, rabbit, pig, and human (groups A, B, AB, and O; Rh+). Agglutination was observed for broiler chicken, layer hen, quail, rabb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Besides having hemolytic and leukocytic activity, the exotoxin GtxA induces an immune response (Bager et al 2014 (Bager, Persson, et al 2013). G. anatis potentially releases hemagglutinin in OMVs, which is capable of agglutinating avian erythrocytes (Zepeda et al 2009;Ramirez-Apolinar et al 2012;Bager, Persson, et al 2013;Johnson et al 2013;Bager et al 2014). OMVs from G. anatis induce a considerable immune response (Pors, Pedersen, et al 2016 (Lintermans et al 1991;Bougu enec & Bertin 1999).…”
Section: Virulence Factors Of G Anatismentioning
confidence: 99%
“…Besides having hemolytic and leukocytic activity, the exotoxin GtxA induces an immune response (Bager et al 2014 (Bager, Persson, et al 2013). G. anatis potentially releases hemagglutinin in OMVs, which is capable of agglutinating avian erythrocytes (Zepeda et al 2009;Ramirez-Apolinar et al 2012;Bager, Persson, et al 2013;Johnson et al 2013;Bager et al 2014). OMVs from G. anatis induce a considerable immune response (Pors, Pedersen, et al 2016 (Lintermans et al 1991;Bougu enec & Bertin 1999).…”
Section: Virulence Factors Of G Anatismentioning
confidence: 99%
“…Currently two biovars have been reported based on their haemolytic property, among which G. anatis biovar haemolytica is pathologically significant compared with non-haemolytic G. anatis biovar anatis (Bojesen & Shivaprasad, 2007;Neubauer et al, 2009). Potential virulence factors of the pathogenic biovar include a cytolytic RTX toxin GtxA, metalloproteases capable of degrading chicken IgG, F-17-like fimbriae and the haemagglutinating property on chicken erythrocytes (García-Gómez et al, 2005;Zepeda et al, 2009;Kristensen et al, 2010;Bager et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Other virulence associated traits among G. anatis strains have been identified, such as protease production and hemagglutination, but the underlying genetic traits responsible for these phenotypes have not yet been determined. It has also been proposed that G. anatis isolates vary in their virulence potential [11], [12], and amplified fragment length polymorphism (AFLP) has revealed that there is substantial genetic diversity among the Gallibacterium isolates dominating among and between successive flocks [13]. The purpose of this study was to generate and compare the genome sequences of virulent and avirulent G. anatis isolates to better understand their genetic composition, and to develop a multilocus sequence typing (MLST) procedure for assessing the genetic relatedness of G. anatis isolates and their genomic content [14].…”
Section: Introductionmentioning
confidence: 99%